Soldados de Caso Rosendi : poemario de un “sobremuriente”. Guerra de Malvinas y poesía : experiencias, identidades, memorias - Andrea Belén Rodríguez (Nuevo mundo - Mundos Nuevos, 2012)
Wars are extreme events that let a mark on the societies that lived them as a whole, and primarily on those who survived, the civilians and military that fought in them. To the ex-combatants, war experience is a landmark in their lives since it is an extreme experience in which the option kill and/or die is a constant, and so they try to elaborate it in the postwar years turning to different languages. The present article is about one of the classic languages that the veterans of several wars along history have appealed to : poetry. More precisely, it address the marks that the conflict between Great Britain and Argentina for the South Atlantic islands let on the lives, identities and memories of the ex-combatants, and, in order to do so, it analyzes “Soldados”, the collection of poems written by Gustavo Caso Rosendi, an ex-conscript that fought on the Malvinas islands in 1982.